Pengaruh Beban Kerja, Lingkungan Kerja Dan Self Efficacy Terhadap Kinerja Karyawan Gen Z PT. Telang Agro Mandiri (TAM) Desa Telang Sari Kabupaten Banyuasin - Siska Permata Sari; Sabeli Aliya (CV. ITTC INDONESIA, 2025)
The dominance of Generation Z in today’s workforce has transformed how companies perceive organizational dynamics and human resource management. PT. Telang Agro Mandiri, an agribusiness company based in Banyuasin Regency, is among the entities facing challenges in adjusting workloads, fostering a supportive work environment, and enhancing employees’ self-efficacy, particularly among young workers. This study aims to analyze the influence of workload, work environment, and self-efficacy on the performance of Generation Z employees at PT. Telang Agro Mandiri. A quantitative approach with an associative-causal design was employed, involving 77 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The findings indicate that workload has a positive and significant effect on employee performance (t = 4.939; p = 0.000), the work environment also shows a positive and significant influence (t = 2.441; p = 0.017), and self-efficacy likewise contributes positively and significantly (t = 2.823; p = 0.006). Simultaneously, the three variables exert a positive and significant impact on Generation Z employee performance (F = 30.131; p = 0.000). These results highlight the importance of PT. Telang Agro Mandiri’s management in ensuring fair workload distribution, cultivating a conducive work environment, and strengthening employee confidence through continuous training and development to enhance Generation Z performance.